Pengaruh kecerdasan emosional, motivasi dan pelatihan terhadap kinerja pegawai Badan Pertanahan Kota Medan - Febriansyah Harahap; Sinto; M. Umar Maya Putra (BONANZA : Jurnal Ilmiah Ekonomi, Bisnis dan Keuangan, 2026)
This study aims to analyze the influence of emotional intelligence, motivation, and training on the performance of employees at the Medan City Land Agency. The background of this research is the importance of integrated human resource management strategies to improve productivity and the quality of public services in the era of Industry 5.0. The research employed a quantitative descriptive approach with a survey method. The sample consisted of 65 employees selected through slovin sampling. The research instrument was a questionnaire, and the data were analyzed using multiple linear regression with the assistance of SPSS software. The findings revealed that emotional intelligence, motivation, and training, both partially and simultaneously, have a positive and significant effect on employee performance. The results indicate that enhanced emotional intelligence enables employees to manage emotions and collaborate effectively; high work motivation drives the achievement of targets; and relevant training improves both technical and non-technical competencies. The synergy of these three factors promotes optimal performance. Emotional intelligence, motivation, and training are strategic factors in improving employee performance. It is recommended that the agency continuously strengthen its human resource development programs in a sustainable and measurable manner.